Proximate Composition, Phytochemical and Antimicrobial Activities of The Fermented Ripe Fruit of Musa Paradisiaca - Falana, Mansurat Bolanle; Nurudeen, Quadri Olaide (Journal of Science and Technology, 2023)
Fermentation alters the physical and chemical components of foods by enhancing their nutrients and synthesizing bioactive composition. To determine the impact of fermentation, ripe Musa paradisiaca (Plantain) fruit used as food and medicine across the globe was fermented and analyzed for pH, proximate composition, preliminary phytochemical constituents, in vitro antimicrobial activities, and active constituents by High-Performance Liquid Chromatography (HPLC). The pH of the sample dropped from 6.7 to 4.7 during fermentation while alkaloids, flavonoids, glycosides, saponins, steroids, tannins, and terpenoids were recorded. Moisture (7.84%), ash (2.10%), fat (7.28%), carbohydrate (86.4%), fiber (1.42%), and protein (2.24%) were present.  Bactericidal (12.5-50.0 mg/mL against Staphylococcus aureus and Escherichia coli, respectively) and fungicidal activities (12.5-25.0 mg/mL against Candida albicans) were noted. At 25, 50, and 100 mg/mL sample concentrations, diameters of 7.00 mm, 10.00 mm, and 16.00 mm were recorded against C. albicans, E. coli, and S. aureus. Capsaicin, caffeic acid, beta-sitosterol, kaempferol, apigenin, syringin, quercetin, and luteolin were detected by HPLC. Consequently, the fermented ripe fruits of M. paradisiaca harbours active constituents and exhibit antimicrobial activities making them curative against pathogens.